Assessment of fuel efficiency of neem biodiesel (Azadirachta indica) in a single cylinder diesel engine. (1st January 2013) - Mathiyazhagan, M.; Elango, T.; Senthilkumar, T.; Ganapathi, A.
Increase of petroleum diesel usage and its environmental pollution necessitate the study of alternate fuel production. Vegetable oils are the viable alternate form of non-polluted, renewable fuel to diesel engines. In this work, the non-edible oil, neem ( Azadirachta indica ) was used to produce biodiesel by a two step transesterification process. The fuel properties of the biodiesel thus produced were determined by standard methods. It is further tested in a single cylinder diesel engine by mixing with petroleum diesel in various percentages. The brake thermal efficiency (BTE) and specific fuel consumption (SFC) of the engine running with biodiesel blends (10–50%) were compared with the petroleum diesel. The results have shown that the performance of the diesel engine was similar as that of normal diesel and thus the use of biodiesel in diesel engine is viable.